JOB DESCRIPTION- RELATED DIFFERENCES IN WORK SAFETY PERCEPTIONS OF THE WORKERS IN CONSTRUCTION INDUSTRY - İkbal Erbaş (Journal of Asian Architecture and Building Engineering, 2022)
The construction sector is a challenging sector where many stakeholders have to work together to ensure occupational health and safety. Workers are the most important actors in ensuring a safe climate. Therefore, the workers’ perceptions of work safety are very substantial in a construction site. This study aims to investigate the work safety perceptions of the workers having different job descriptions in the construction industry. A questionnaire was applied to 130 workers in different job positions at a residential building construction site in Turkey. The workers’ perceptions were asked in four categories: construction work safety, coworkers’ safety attitude, occupational health and safety specialists’ safety attitude, and site manager’s safety attitude. For analysis, the relative importance index was calculated, and ANOVA analysis was used. The results showed that (1) the workers’ work safety perceptions were limited with their job description, (2) the cultural structure of the employees may prevent workers from being impartial in evaluating safety issues, (3) and considering different workgroups’ safety needs and ensuring participation in the safety issues are compulsory for safety managers. The findings of the study are expected to contribute to improvements in safety management practices of safety management actors.